INFORMATION SEEK BEHAVIOUR OF CANCER PATIENTS IN PALLIATIVE CARE IN NORTHERN NIGERIA (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study assessed information seek behaviour of cancer patients in palliative care in Northern Nigeria. The study was guided with two hypotheses. Survey research design was used for this study. The population for this study comprise all patients in palliative care attending Usman Danfudio Teaching Hospital, Sokoto; Ahmadu Bello University Teaching Hospital, Zaria and National Hospital, Abuja the three (3) hospital were purposively selected because they are the only University Teaching Hospital that offer radiotherapy in Northern Nigeria and a total of five hundred and eighty four (584) (University Teaching Hospital). Availability sampling procedure was used for the study. Split half reliability method was employed to test the reliability of the instrument and the reliability index of 0.85 was obtained. Analysis of data was done using descriptive statistics of mean, standard deviation, frequency counts and percentage. t-test and chi-squre was used to test hypotheses at 0.05 alpha level of significance. The results indicated that there is significant difference in information seeking behaviour of cancer patients in palliative care in Northern Nigeria (P < 0.05) and there is no significant difference between male and female on information seeking behaviour of cancer patients in palliative care in Northern Nigeria (P>0.05). it was recommended that Government and health workers should organise programs for cancer patients in palliative care in Northern Nigeria so as to spread awareness that will make cancer patients acquire correct information on management of cancer.